Forced retirement from professional Rugby Union is associated with symptoms of distress - Brown, J. C.; Kerkhoffs, G.; Lambert, M. I.; Gouttebarge, V. (International Journal of Sports Medicine, 2017)
Rugby has a higher injury burden than other popular sports, such as football. Athletes who are forced to retire as a result of injury are associated with poor mental health. With its high injury burden, professional rugby players might be at risk of mental health conditions associated with injury-related forced retirement. This study aimed to compare mental health between former professional rugby players who were and weren`t forced to retire. A questionnaire including the 4DSQ (distress), GHQ-12 (anxiety/depression), PROMIS short-form (sleep disturbance) and AUDIT-C (alcohol misuse) was completed by retired professional players from Ireland, France and South Africa. The questionnaire asked players whether or not they were forced to retire, as well as the reason for retirement. Players forced to retire were more than twice as likely to report symptoms of distress in comparison to those that retired voluntarily (odds ratio: 2.1, 95% confidence interval: 1.2-3.6, p<0.001). None of the other mental health measures (anxiety/depression, sleep disturbance or alcohol misuse) were associated with forced retirement. In conclusion, rugby players that were forced to retire may require support structures and longitudinal monitoring. Future studies should begin monitoring players during their careers to accurately assess the effect of retirement on mental health.